Perancangan Aplikasi Pendeteksi Uang Kertas Asli/Palsu Menggunakan OpenCV Dan PyQt - Safitri, Alifiana; Brian Prawira, Faried; Tulfah, Khairullah; Aditya, Yoga; Rosyani, Perani (CV. Shofanah Media Berkah, 2024)
Detecting counterfeit banknotes is a significant issue in the financial and banking sectors. This paper presents the design and implementation of an application for counterfeit banknote detection using OpenCV and PyQt. OpenCV is employed for image processing, while PyQt is utilized for developing the graphical user interface. The system aims to provide an efficient and accurate solution for detecting counterfeit banknotes. Various types of banknotes were tested to evaluate the system's performance. The results indicate that the system can detect counterfeit banknotes with high accuracy.